Toughening of linear low-density polyethylene/brominated polystyrene blend by styrene-ethylene/butylene-styrene elastomer. (17th April 2023) - Jiang, Zhiyuan; Chen, Hengxi; Zhao, Mingzhen; McCarney, Jonathan; De Schryver, Daniel; Aplin, Todd; Sue, Hung-Jue
Abstract: Brominated polystyrene (BPS) is blended with linear low-density polyethylene (LLDPE) to improve its fire retardancy for various applications such as wire and cable covering. To improve compatibility and mechanical properties, styrene-ethylene/butylene-styrene (SEBS) copolymer was added as a compatibilizer. The influence of processing temperature and SEBS elastomer on morphology, interfacial and mechanical properties has been investigated. It was found that melt blending at 230 °C with addition of SEBS elastomer can significantly reduce the BPS particle size to less than 0.5 μm by forming a core-shell structure that enhances the interfacial strength between BPS and LLDPE phases. Addition of 8 phr SEBS elastomer can increase the Izod impact strength at −37 °C by a factor of nearly three, compared to the non-compatibilized LLDPE/BPS system. Double-notch four-point bending (DN-4PB) test reveals that crazing and shear banding are two primary toughening mechanisms for the observed increase in the low temperature impact strength. Graphical abstract: Image 1 Highlights: LLDPE/BPS blends were successfully compatibilized and toughened by a SEBS rubber. A core-shell structure was formed with BPS particle size reduced to less than 0.5 μm. Processing temperature is vital to obtain fine morphology due to viscosity match. Izod impact strength at −37 °C is improved by about 3 times with 8 wt% SEBS added. Crazing and shear banding are primary toughening mechanisms.